Indomethacin Treatment of Mice with Premalignant Oral Lesions Sustains Cytokine Production and Slows Progression to Cancer - Johnson, Sara D.; Young, M. Rita I. (Frontiers in Immunology, 2016)
Current treatment options for head and neck squamous cell carcinoma (HNSCC) patients are often ineffective due to tumor localized and systemic immunosuppression. Using the 4-NQO mouse model of oral carcinogenesis, this study showed that premalignant oral lesion cells produce higher levels of the immune modulator, PGE2, compared to HNSCC cells. Inhibiting prostaglandin production of premalignant lesion cells with the pan-cyclooxygenase inhibitor indomethacin stimulated their induction of spleen cell cytokine production. In contrast, inhibiting HNSCC prostaglandin production did not stimulate their induction of spleen cell cytokine production. Treatment of mice bearing premalignant oral lesions with indomethacin slowed progression of premalignant oral lesions to HNSCC. Flow cytometric analysis of T cells in the regional lymph nodes of lesion-bearing mice receiving indomethacin treatment showed an increase in lymph node cellularity and in the absolute number of CD8+ T cells expressing IFN-γ compared to levels in lesion-bearing mice receiving diluent control treatment. The cytokine-stimulatory effect of indomethacin treatment was not localized to regional lymph nodes but was also seen in the spleen of mice with premalignant oral lesions. Together, these data suggest that inhibiting prostaglandin production at the premalignant lesion stage boosts immune capability and improves clinical outcomes.